2022
DOI: 10.1136/bmjopen-2021-055046
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour changes and HIV infection among men who have sex with men: evidence from an open cohort in China

Abstract: BackgroundThe HIV epidemic in key populations such as men who have sex with men (MSM) is a public health issue of worldwide concern. China has seen an increase in newly diagnosed HIV infections through male–male sexual contact in the past decade. In a long-term cohort, how the complex behaviour pattern of MSM changed and the association with the HIV risk are unclear at present.MethodsThis study was conducted from October 2011 to December 2019 in Tianjin. MSM were recruited by snowball sampling through online a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, most studies about HIV among MSM have primarily used cross-sectional designs [ 9-11 ]. Conducting prospective cohort studies is recommended to estimate HIV incidence, as they provide more precise and reliable data to monitor trends in the HIV epidemic and to evaluate the effectiveness of HIV prevention and control efforts [ 12 13 ]. An open cohort study in Beijing, the capital of China, observed an HIV incidence of 5.9 (95% CI 4.6-7.6) per 100 person-years (PYs) among MSM with an overall retention rate of 69.7% (699/1003) from 2009 to 2012 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies about HIV among MSM have primarily used cross-sectional designs [ 9-11 ]. Conducting prospective cohort studies is recommended to estimate HIV incidence, as they provide more precise and reliable data to monitor trends in the HIV epidemic and to evaluate the effectiveness of HIV prevention and control efforts [ 12 13 ]. An open cohort study in Beijing, the capital of China, observed an HIV incidence of 5.9 (95% CI 4.6-7.6) per 100 person-years (PYs) among MSM with an overall retention rate of 69.7% (699/1003) from 2009 to 2012 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%